Potential involvement of DSCAML1 mutations in neurodevelopmental disorders. (18th February 2021) - Ogata, Shigehiro; Hashizume, Koichi; Hayase, Yoneko; Kanno, Yukie; Hori, Kei; Balan, Shabeesh; Yoshikawa, Takeo; Takahashi, Hidehiko; Taya, Shinichiro; Hoshino, Mikio
Abstract: The molecular mechanisms underlying neurodevelopmental disorders (NDDs) remain unclear. We previously identified Down syndrome cell adhesion molecule like 1 ( Dscaml1 ) as a responsible gene for Ihara epileptic rat (IER), a rat model for human NDDs with epilepsy. However, the relationship between NDDs and DSCAML1 in humans is still elusive. In this study, we screened databases of autism spectrum disorders (ASD), intellectual disability (ID)/developmental disorders (DD) and schizophrenia for genomic mutations in human DSCAML1 . We then performed in silico analyses to estimate the potential damage to the mutated DSCAML1 proteins and chose three representative mutations (DSCAML1 C729R, DSCAML1 R1685* and DSCAML1 K2108Nfs*37 ), which lacked a cysteine residue in the seventh Ig domain, the intracellular region and the C‐terminal PDZ‐binding motif, respectively. In overexpression experiments in a cell line, DSCAML1 C729R lost its mature N‐glycosylation, whereas DSCAML1 K2108Nfs*37 was abnormally degraded via proteasome‐dependent protein degradation. Furthermore, in primary hippocampal neurons, the ability of the wild‐type DSCAML1 to regulate the number of synapses was lost with all mutant proteins. These results provide insight into understanding the roles of the domains in the DSCAML1 protein and further suggest that these mutations cause functional changes, albeit through different mechanisms, that likely affect the pathophysiology of NDDs. Abstract : Genomic mutations in human DSCAML1 were identified from databases of ASD, ID/DD and schizophrenia. The mutations affected the functions of DSCAML1 protein in cell–cell adhesion and synapse number restriction. This study gives clues to understanding the pathophysiology of neurodevelopmental disorders.